Improving ankle dorsiflexion as a preventive tool for athletes - Falcone, G.; Ceciliani, A.; Izzo, R.; D'Elia, F. (Journal of Human Sport & Exercise, 2019)
Basketball, such as soccer and volleyball, has the issue to rehabilitation too deep for re athletisation early. The work carried out aims to demonstrate how improving dorsal flexion of the ankle is an excellent tool for the prevention of all injuries for athletes who play basketball. This study has as a sample a group of 12 athletes aged between 16 and 18 years who in the past have found, albeit mildly, problems with the lower limbs linked to reduced mobility of the ankle joint, as demonstrated by the tests that were performed on each subject of the chosen group. The work protocol chosen for the aforementioned group was submitted to each subject three days a week for the duration of two months. The exercises performed were exercises of myofascial release, passive mobility, proprioception and dynamic stretching. All the athletes have meticulously carried out the work protocol and in the end, from the data that emerged, a general improvement of the subjects involved in the protocol can be seen, above all by the most suffering and most frequently exposed to injury. Specifically, the data showed an increase in dorsiflexion of 3.1% for the left ankle and 6.2% for the right ankle.